Motywacja jako czynnik uprawiania sportu wśród studentów Uniwersytetu Kazimierza Wielkiego w Bydgoszczy = Motivation as a factor in sports among the students of the Kazimierz Wielki University in Bydgoszcz - Kotecka, Klaudia; Cieślicka, Mirosława; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kotecka Klaudia, Cieślicka Mirosława, Zukow Walery. Motywacja jako czynnik uprawiania sportu wśród studentów Uniwersytetu Kazimierza Wielkiego w Bydgoszczy = Motivation as a factor in sports among the students of the Kazimierz Wielki University in Bydgoszcz. Journal of Education, Health and Sport. 2016;6(8):467-488. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60922 http://ojs.ukw.edu.pl/index.php/johs/article/view/3781 https://pbn.nauka.gov.pl/sedno-webapp/works/744750 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. Motywacja jako czynnik uprawiania sportu wśród studentów Uniwersytetu Kazimierza Wielkiego w Bydgoszczy Motivation as a factor in sports among the students of the Kazimierz Wielki University in Bydgoszcz Klaudia Kotecka, Mirosława Cieślicka, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Ankieta przeprowadzona wśród studentów Uniwersytetu Kazimierza Wielkiego w Bydgoszczy była wiarygodnym źródłem odpowiedzi. W ankiecie wzięło udział 108 respondentów z czego 17,6% stanowiły kobiety a 82,4% mężczyźni. Przedział wiekowy odpowiadających to 19-27 lat. Analiza otrzymanych wyników wykazała, że zdecydowanie większa część ankietowanych studentów przykłada wagę do własnej sprawności fizycznej. Studenci, którzy wykonują ćwiczenia ruchowe trzy razy w tygodniu i więcej stanowili 36% wszystkich respondentów. Najczęściej studenci podejmują aktywność fizyczną na wolnym powietrzu. Badania wykazują, że ankietowani czują satysfakcję i radość po zakończeniu ćwiczeń. Innymi istotnymi czynnikami, które motywują studentów Uniwersytetu Kazimierza Wielkiego są: poprawa ogólnej sprawności fizycznej, poprawa stanu psychicznego oraz samopoczucia. Dla wielu studentów motywacją jest poprawa stanu zdrowia czy odpoczynek od obowiązków. Niewielu studentów podejmuje aktywność fizyczną poprzez namowę znajomych czy chęć opóźnienia procesu starzenia. Słowa kluczowe: motywacja, aktywność fizyczna, sport, studenci. Abstract A survey of students at the Kazimierz Wielki University Bydgoszcz was a reliable source of answers. The survey was attended by 108 respondents of which 17.6% were women and 82.4% men. The age range corresponding to 19-27 years. Analysis of the results showed that by far the majority of the students surveyed pays attention to their own physical fitness. Students who perform physical exercises three times a week or more accounted for 36% of all respondents. Most often students take physical activity outdoors. Studies show that respondents feel the satisfaction and joy after exercise. Other important factors that motivate students Kazimierz Wielki University are to improve overall physical fitness, improving mental health and well-being. For many students the motivation is to improve the health of the rest of the duties. Few students take physical activity through the urging of friends or wanting to delay the aging process. Key words: motivation, physical activity, sport, students.